Perfil nutricional e desfechos em pacientes com condições crônicas complexas admitidos em uma unidade de terapia intensiva pediátrica - Andrades, Gabriela Rupp Hanzen (2020)
Introduction: In Pediatric Intensive Care Units (PICUs) there is a high prevalence of patients with some complex chronic condition (CCC). In children and adolescents, the presence of CCC can result in changes in nutritional status (NS), such as weight inadequacy and growth deficit. Objectives: To assess the nutritional status of patients with CCC admitted to the PICU, and the relationship with outcomes: length of stay (LOS), need for mechanical ventilation (MV), organ dysfunction and mortality. Methods: Retrospective cohort study with patients admitted to a PICU from January 2013 to December 2017. Body mass index for age (BMI/A) and height for age (H/A), having as reference the curves of the World Health Organization categorized as “underweight”, “overweight” and “adequate weight”. The presence of CCC was recorded according to the criteria of Feudtner et al. Outcomes such as mortality, MV, multiple organ dysfunction syndrome (MODS) and LOS in the unit were assessed. Severity was measured using the Pediatric Index of Mortality 2 (PIM2) score. The comparison analysis between the NS categories was performed using Pearson's Chi-square and Kruskall-Wallis tests, with Bonferroni correction. Results: 1753 admissions were included. The presence of CCC represented 49.8% (873) of the sample. Among patients with CCCs, 61.7% (539) of the individuals were classified as normal weight, 19.8% (173) were underweight and 18.4% (161) overweight. H/A was considered inadequate in 32.2% of patients with CCC, having a higher proportion when compared to patients without the presence of CCC 25.3% (p<0.001). In the analysis of the outcomes, underweight patients had prolonged LOS (p<0.001) when compared to the appropriate weight and overweight groups (p<0.001). Overweight patients needed less MV when compared to the adequate and underweight groups (p<0.001). MODS was found in 57.2% of patients in the underweight group, compared to 45.5% of adequate weight and 47.2% of overweight. There was no association between the three weight categories with mortality (p=0.2), however, in the descriptive analysis, this was higher in the underweight group. Conclusion: The inadequacies of NS in patients with CCCs are representative in PICU admissions. Low weight patients had a higher risk of mortality, more organ dysfunction and prolonged LOS. Those who were classified as overweight had less need for MV. These results suggest that the assessment of nutritional status should be performed on admission to the PICU to identify weight inadequacies in children with CCC so that they can benefit from an adequate nutritional intervention.